El componente teórico en la producción científica / ABSTRACT Although scientific production is a product, is also a process; achieve more systematic, relevance, scientific approach and organization become key for the research that represents true contributions and advances in science, from the research whatever. Here, within this process of producing science, there are several components; one of them is the theoretical component, which represents one of the pillars of scientific development. The purpose of this paper is to present a descriptive and explanatory view of the role of theory in scientific production component; achieve notions establish logical and reasonable theory of why we employ in our investigations, or even - more - why or submit to generate contrast, is one of the great journeys that every researcher must perform. Hence, for a researcher to understand the scientific processes must recognize the purpose and value of theory in research, he is the same one that generates or has a good chance to evaluate. - Leal, Lionel; Rincón, Oriana (Impacto Científico, 2020)
ResumenAunque la producción científica supone un producto, es a la vezun proceso; lograr la mayor sistematicidad, relevancia, cientificidad yorganización se convierten en aspectos clave para que las investigacioneslleguen a representar verdaderos aportes y avances para la ciencia, desdela línea de investigación que sea. En este sentido, dentro de este procesode producir ciencia, se encuentran varios componentes, siendo uno de ellosel componente teórico, el cual representa uno de los pilares del desarrollocientífico. El propósito de este trabajo es presentar una visión descriptiva delpapel del componente teórico en la producción científica; lograr establecernociones lógicas y razonables del por qué empleamos teoría en nuestrasinvestigaciones, o más aun por qué la generamos o sometemos a contraste,es una de las grandes travesías que todo investigador debe realizar. De allíque para que un investigador entienda los procesos científicos debe reconocer el propósito y valor de la teoría dentro de la investigación, sea la que él mismo genere o aquella que a bien tenga la oportunidad de evaluar.ABSTRACTAlthough scientific production is a product, is also a process; achieve moresystematic, relevance, scientific approach and organization become key forthe research that represents true contributions and advances in science, from the research whatever. Here, within this process of producing science, there are several components; one of them is the theoretical component, which represents one of the pillars of scientific development. The purpose of this paper is to present a descriptive and explanatory view of the role of theory in scientific production component; achieve notions establish logical and reasonable theory of why we employ in our investigations, or even - more - why or submit to generate contrast, is one of the great journeys that every researcher must perform. Hence, for a researcher to understand the scientific processes must recognize the purpose and value of theory in research, he is the same one that generates or has a good chance to evaluate.